Effects of olanzapine on 31P MRS metabolic markers in schizophrenia. (7th December 2012) - Nenadic, Igor; Dietzek, Maren; Langbein, Kerstin; Rzanny, Reinhard; Gussew, Alexander; Reichenbach, Jürgen R.; Sauer, Heinrich; Smesny, Stefan
Abstract : Antipsychotic drug action might include mechanisms related to normalising phospholipid and high‐energy metabolism. We applied brain metabolic imaging with 31 P magnetic resonance spectroscopy ( 31 P MRS) and two‐dimensional chemical shift imaging to assess changes of metabolism of phospholipids and high‐energy phosphates in schizophrenia patients at baseline (four antipsychotic‐naïve and three off antipsychotics) and at follow‐up, after 6 weeks of treatment with olanzapine. Results indicate a significant increase of adenosine‐triphosphate (ATP) in the right inferior temporal cortex and a trend towards ATP decrease in the left cerebellum. This suggests a shift in high‐energy phosphates (rather than phospholipids), possibly related to normalisation of functioning in these areas. Copyright © 2012 John Wiley & Sons, Ltd.